Pengenalan Aspek Ergonomi pada Penataan Operasional Bongkar Muat Pasar Giwangan Yogyakarta - Santoso, Prasidananto Nur; Astuti, Marni; Nurdin, Riani; Sullyartha, Esa Rengganis; Mauidzoh, Uyuunul; Gunawan, Gunawan; Poerwanto, Eko; Zabidi, Yasrin; Budiwidodo, Sidik (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Traditional markets act as food-logistics nodes with intensive unloading activities and manual handling that may increase musculoskeletal risk, internal congestion, and reduced accessibility due to layout and hygiene issues. This community-service paper is developed from a field assessment at Pasar Giwangan, Yogyakarta, conducted during 3 months (April–June 2020), and translated into an ergonomics socialization package, critical point mapping of circulation, and practical recommendations for loading and unloading operations. Key findings include heavy carrying (>50 kg) by informal porters with 2–5 repetitions per task, peak-hour congestion, reduced effective lane width caused by access configuration, and improper waste disposal that disturbs comfort and mobility. Proposed outputs include OSH ergonomics materials, strengthening handling aids (trolleys), and circulation/zonation adjustments for unloading activities.